Differences in Paramedic Fatigue before and after Changing from a 24-hour to an 8-hour Shift Schedule: A Case Report. (2nd January 2016) - Patterson, P. Daniel; Klapec, Sharon E.; Weaver, Matthew D.; Guyette, Francis X.; Platt, Thomas E.; Buysse, Daniel J.
Abstract: Emergency medical services (EMS) clinicians often work 24-hour shifts. There is a growing body of literature, with an elevated level of concern among EMS leaders that longer shifts contribute to fatigued workers and negative safety outcomes. However, many questions remain about shift length, fatigue, and outcomes. We describe a case of a 26-year-old male paramedic who switched shift schedules during the midpoint of a randomized trial that addressed fatigue in EMS workers (clinicaltrials.gov identifier: NCT02063737). The participant (case) began the study working full-time with a critical care, advanced life support EMS system that utilized 24-hour shifts. He then transitioned to an EMS system that deploys workers on 8-hour shifts. Per protocol for the randomized trial, the participant completed a battery of sleep health and fatigue surveys at baseline and at the end of 90 days of study. He also reported perceived fatigue, sleepiness, and difficulty with concentration at the beginning, every 4 hours during, and at the end of scheduled shifts, for a total of ten 24-hour shifts and twenty-four 8-hour shifts. We discuss differences in measures taken before and after switching shift schedules, and highlight differences in fatigue, sleepiness, and difficulty with concentration taken at the end of all 34 scheduled shifts stratified by shift duration (24 hours versus 8 hours). Findings from this case report present a unique opportunity to 1) observe and analyze a phenomenon that has not been investigated in great detail in the EMS setting; and 2) address an issue of significance to employers and EMS clinicians alike.